2011
DOI: 10.1111/j.1439-0469.2010.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological factors determining Tardigrada distribution in Costa Rica

Abstract: Over 700 moss, lichen and hepatic samples were collected from territory of Costa Rica. Tardigrades were present in nearly half of the samples. Overall, more than 7000 tardigrades were found. All specimens were identified as 64 species belonging to 18 genera. The number of species per positive sample varied between 1 and 10, but on average it did not exceed three. The most important factor influencing distribution of Tardigrada in Costa Rica was altitude. Tardigrades most often inhabited mosses, lichens and hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…The growth form of a moss or lichen, and its effect on micro-environmental conditions (i.e., moisture), is probably more significant than the substrate species (e.g., Jö nsson 2003Jö nsson , 2007Meyer 2006a;Guil, Hortal et al 2009;). Still, the overall meso-climatic regimes of the environment in which the cryptogam grows (such as rainfall, humidity, exposure, insulation and temperature) seem to be chiefly responsible for the development and maintenance of tardigrade populations (Schuster & Greven 2007;Guil, Hortal et al 2009;Kaczmarek, Gołdyn, Wełnicz et al 2011). It therefore seems reasonable to conclude that neither the type of vegetation nor differences in moss and lichen species significantly influenced tardigrade composition along the altitudinal gradients investigated in the present study.…”
Section: Altitude and Tardigrade Distributioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The growth form of a moss or lichen, and its effect on micro-environmental conditions (i.e., moisture), is probably more significant than the substrate species (e.g., Jö nsson 2003Jö nsson , 2007Meyer 2006a;Guil, Hortal et al 2009;). Still, the overall meso-climatic regimes of the environment in which the cryptogam grows (such as rainfall, humidity, exposure, insulation and temperature) seem to be chiefly responsible for the development and maintenance of tardigrade populations (Schuster & Greven 2007;Guil, Hortal et al 2009;Kaczmarek, Gołdyn, Wełnicz et al 2011). It therefore seems reasonable to conclude that neither the type of vegetation nor differences in moss and lichen species significantly influenced tardigrade composition along the altitudinal gradients investigated in the present study.…”
Section: Altitude and Tardigrade Distributioncontrasting
confidence: 51%
“…A significant relationship between the structure of tardigrade communities and elevation has been documented by a number of studies (e.g., RodriguezRoda 1951;Nelson 1975;Dastych 1980Dastych , 1985Dastych , 1987Dastych , 1988Beasley 1988;Collins & Bateman 2001;Guil, Hortal et al 2009;Kaczmarek, Gołdyn, Wełnicz et al 2011). However, it is not clear which variables covarying with elevation (e.g., climate, vegetation or others) are responsible for shaping tardigrade diversity, distribution and abundance.…”
Section: Altitude and Tardigrade Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bartels and Nelson (2006) observed that tardigrade species' richness was always lower in lichens than in mosses in Great Smoky Mountains National Park (North Carolina, Tennessee, USA). Additionally, a study conducted in Costa Rican rainforests revealed that plant type had the weakest influence on tardigrade distribution (Kaczmarek et al 2011b). …”
Section: Discussion Tardigrada Abundance and Species Compositionmentioning
confidence: 99%
“…120, and Romania ca. 140 (see Degma, 2006;Kaczmarek et al 2010aKaczmarek et al , 2010bKaczmarek et al, 2012;Vargha, 2012;Zawierucha et al, 2013;Ciobanu et al, 2014;Coulson et al, 2014;Lisi et al, 2014). Knowledge on the tardigrade fauna of Colombia also looks very poor in comparison with knowledge of tardigrade fauna of Central and South America (100 species known from Central America, 220 from South America, and 251 from the entire Neotropical region) (Meyer, 2013;Kaczmarek et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%